Development of Geographic Information System (GIS) database for recreation facilities in Tasik Awam Bandar Tenggara, Kulai, Johor / Mohamad Afif Faiq Zaini - Zaini, Mohamad Afif Faiq (Universiti Teknologi Mara, Perak, 2021)
The study is being conducted about the development of Geographic Information System (GIS) database of recreational facilities in Tasik Awam Bandar Tenggara, Kulai, Johor. It is analysing the condition and facilities taypes for recreation facilities in the study area. The study covered the whole of Tasik Awam Bandar Tenggara with 9.87 hectare (24.4 acres). The literature review is based on research from the others article and journal from internet as mentioned earlier. There are six stages in the research process, start from the background of the study, and the last is recommendations and conclusion. The methods used to carry out the study are based on the survey form and observation survey and secondary data, which is Garis Panduan Pembangunan Tanah Lapang dan Kawasan Rekreasi, 2013, Rancangan Tempatan Majlis Daerah Kota Tinggi, and Lembaga Kemajuan Johor Tenggara (KEJORA). Finding from this analysis will be the basic preparation to make an appropriate recommendation and conclusion. All recommendation that has been made is to provide the GIS database development on recreational facilities condition and types in Tasik Awam Bandar Tenggara, Kulai, Johor.